Private law in the external relations of the EU - Cremona, Marise; Micklitz, Hans-W. (Oxford : Oxford University Press, 2016)
This edited volume explores the interaction between EU external relations law and private law, examining how the relationship has affected the evolution of the EU's competence, the extent of EU private law's reach beyond the boundaries of an internal market, and how the EU contributes to the formation of private regulation at an international level.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 2, 2016).
Keywords: European Union countries -- Foreign relations -- Law and legislation; Civil law -- European Union countries; Law; International law